Assessing capacities and resilience of health services during the COVID-19 pandemic: Lessons learned from use of rapid key informant surveys - Rivas-Morello, Briana; Horemans, Dirk; Viswanathan, Kavitha; Taylor, Chelsea; Blanchard, Andrea; Karamagi, Humphrey; Droti, Benson; Titi-Ofei, Regina; Nikiema, Laetitia Ouedraogo; Traore, Moussa; Kipruto, Hillary; del Riego, Amalia; et al. (Frontiers in Public Health, 2023)
This article is part of the Research Topic ‘Health Systems Recovery in the Context of COVID-19 and Protracted Conflict.’ Problem Many countries lacked rapid and nimble data systems to track health service capacities to respond to COVID-19. They struggled to assess and monitor rapidly evolving service disruptions, health workforce capacities, health products availability, community needs and perspectives, and mitigation responses to maintain essential health services. Method Building on established methodologies, the World Health Organization developed a suite of methods and tools to support countries to rapidly fill data gaps and guide decision-making during COVID-19. The tools included: (1) a national “pulse” survey on service disruptions and bottlenecks; (2) a phone-based facility survey on frontline service capacities; and (3) a phone-based community survey on demand-side challenges and health needs. Use Three national pulse surveys revealed persisting service disruptions throughout 2020–2021 (97 countries responded to all three rounds). Results guided mitigation strategies and operational plans at country level, and informed investments and delivery of essential supplies at global level. Facility and community surveys in 22 countries found similar disruptions and limited frontline service capacities at a more granular level. Findings informed key actions to improve service delivery and responsiveness from local to national levels. Lessons learned The rapid key informant surveys provided a low-resource way to collect action-oriented health services data to inform response and recovery from local to global levels. The approach fostered country ownership, stronger data capacities, and integration into operational planning. The surveys are being evaluated to inform integration into country data systems to bolster routine health services monitoring and serve as health services alert functions for the future.